2014
DOI: 10.1097/mcg.0000000000000036
|View full text |Cite
|
Sign up to set email alerts
|

Liver Function Breath Tests for Differentiation of Steatohepatitis From Simple Fatty Liver in Patients With Nonalcoholic Fatty Liver Disease

Abstract: In the NAFLD patients, decreased and delayed liver microsomal function, as assessed by C-ABT, is associated with more severe necroinflammation and fibrosis, whereas C-ABT results at 120 minutes may be helpful for the diagnosis of NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…The reduced albumin may reflect low-grade inflammation with albumin as a negative acute-phase protein or decreased hepatic protein synthetic capacity. These findings are consistent with the few existing data on liver function in human NAFLD (8,19,42).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The reduced albumin may reflect low-grade inflammation with albumin as a negative acute-phase protein or decreased hepatic protein synthetic capacity. These findings are consistent with the few existing data on liver function in human NAFLD (8,19,42).…”
Section: Discussionsupporting
confidence: 95%
“…It has been demonstrated that NASH patients tend to have a reduced activity of liver-derived coagulation factors and lower levels of albumin than patients with pure steatosis (7). Breath tests as indirect measures of liver function suggest some degree of relation between functional impairment and the extent of fatty liver lesions (8,42). The metabolic liver function assessed more directly by the galactose elimination capacity was found to be decreased in steatosis patients (19).…”
mentioning
confidence: 97%
“…13 C‐LFBT also represent dynamic tests with oral consumption or intravenous application of the marker substance and measurement of the end product of hepatic metabolism, that is exhaled 13 CO 2 . Some modifications have been shown to detect early changes in liver metabolic capacity in patients, prior to the presence of structural damage to the liver (i.e., inflammation, fibrosis), 152 though with limited sensitivities and specificities 153–160 . Still, the dynamic nature of 13 C‐LFBT, their possible versatility in terms of assessing a range of different liver functions, and the ease with which they can be repeated to follow relative changes in liver function with time, generally imply a marked potential for clinical application 40 …”
Section: C‐liver Function Breath Testsmentioning
confidence: 99%
“…Some modifications have been shown to detect early changes in liver metabolic capacity in patients, prior to the presence of structural damage to the liver (i.e., inflammation, fibrosis), 152 though with limited sensitivities and specificities. [153][154][155][156][157][158][159][160] Still, the dynamic nature of 13 C-LFBT, their possible versatility in terms of assessing a range of different liver functions, and the ease with which they can be repeated to follow relative changes in liver function with time, generally imply a marked potential for clinical application. 40 When should 13 C-LFBT be utilized?…”
Section: Recommendation 43 Adult Patients Adolescents and Older Childrenmentioning
confidence: 99%
See 1 more Smart Citation